2014
DOI: 10.1177/0300060514543035
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with specific uropathogens in catheter-associated urinary tract infection: Developing a clinical prediction model

Abstract: Objectives: To identify characteristics associated with particular groups of uropathogens in catheter-associated urinary tract infection (CA-UTI) and to develop clinical prediction rules for identifying these groups. Methods: Demographic, clinical and microbiological data were analysed from patients with CA-UTI. Infections were categorized into enteric Gram-negative rods, nonfermenters, Gram-positive cocci and fungal. Variables were analysed using univariate and multiple logistic regression analyses, and were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…UTIs are mostly complicated with various predisposing factors [5]. In more than 80% of the cases, they are related to the use of urologic devices including foley catheters [6], and according to risk factors and clinical settings, there are several described uropathogens [7]. E. coli is reported as the most common pathogen of UTIs, followed by the second most common, K. pneumonia [8].…”
Section: Introductionmentioning
confidence: 99%
“…UTIs are mostly complicated with various predisposing factors [5]. In more than 80% of the cases, they are related to the use of urologic devices including foley catheters [6], and according to risk factors and clinical settings, there are several described uropathogens [7]. E. coli is reported as the most common pathogen of UTIs, followed by the second most common, K. pneumonia [8].…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Switzerland it was found that 1.5% of the catheterized patients developed UTI. 15 This significant difference of occurrence of UTI following urinary catheterization, between the two countries could be due to the strict aseptic measures taken in developed countries for urinary catheterization. Such strict measures should also be taken in the developing countries to reduce occurrence of UTI following urinary catheterization.…”
Section: Discussionmentioning
confidence: 99%
“…and Staphylococci. 64 Higher rates of CAUTIs and antibiotic-resistant organisms have been reported in parts of Asia. Hence, antimicrobial treatment choice should be guided by local antibiograms and culture results (LE: 4).…”
Section: Catheter-associated Utismentioning
confidence: 99%
“…Candida species are the most common uropathogens, followed by Enterococci , E. coli , Pseudomonas spp., Klebsiella spp. and Staphylococci . Higher rates of CAUTIs and antibiotic‐resistant organisms have been reported in parts of Asia.…”
Section: Urinary Tract Infectionsmentioning
confidence: 99%